Exploring the potential of Weissella paramesenteroides UFTM 2.6.1 in disrupting quorum sensing and attenuating virulence in Listeria monocytogenes - Rotta, Isabela Sguilla; Rezende, Sthefânia Dalva da Cunha; Perini, Hugo Felix; da Silva, Marcos Vinicius; de Almeida, Felipe Alves; Pinto, Uelinton Manoel; Ferreira Machado, Alessandra Barbosa; Paiva, Aline Dias (Frontiers in Microbiology, 2025)
IntroductionWeissella paramesenteroides UFTM 2.6.1, isolated from unpasteurized milk, is a potentially probiotic strain exhibiting desirable properties previously demonstrated in vitro, along with a confirmed safe and promising genetic profile based on whole-genome analysis. Due to the limited research on the ability of Weissella species to synthesize compounds with anti-quorum sensing activity, this study aimed to investigate the potential of W. paramesenteroides UFTM 2.6.1 to disrupt quorum sensing (QS) signaling and attenuate the virulence of Listeria monocytogenes, an important foodborne pathogen responsible for the zoonotic disease listeriosis.MethodsThe effects of W. paramesenteroides cell-free supernatant (Wp-CFS) were evaluated on the growth, biofilm formation, motility, and expression of QS- and virulence-related genes in L. monocytogenes.ResultsWp-CFS exhibited bacteriostatic activity against L. monocytogenes strains isolated from food and food processing environments (n = 21). Additionally, it consistently reduced biofilm formation and swarming motility, two well-known QS-regulated phenotypes in L. monocytogenes. Exposure to Wp-CFS (0.25x MIC; 7.81 mg/mL), at 28°C for 24 h, significantly downregulated the relative expression of the genes luxS, agrA, flaA, motA, motB, and degU, whereas the genes sigB, and prfA were upregulated.ConclusionThis study represents the first report demonstrating the production of compounds by W. paramesenteroides aimed at disrupting the QS system of L. monocytogenes, offering novel insights into alternative approaches to attenuate pathogen virulence without relying on traditional antimicrobials.